D-ARM a new proposal for multi-dimensional interconnection networks. - Ling, Lee Luan (Computer communication review.)
This paper presents a new topology for multidimensional interconnection networks, namely D-ARM, which has the goal of simultaneously providing a high network transmission capacity and a low information transfer delay. The new D-ARM topology has a connection pattern arranged in alternated regular mesh fashions with toroidal boundaries. Five distinct network attributes, normally used to characterize interconnection network topologies, were employed to analyze the D-ARM topology: network diameter, bisection width, deflection index, degree of connectivity and symmetry. Also the evaluation of the performance of the D-ARM network through computer simulations was carried out based on the following measures: throughput and information transfer delay. An upper-bound of the network transmission capacity was derived in function of the network dimension (D) and length (W). In order to validate our proposal, as a viable topology among other well-known topologies, a comparative analysis among the D-ARM, MSN and ShuffleNet was performed. The analysis results show that the D-ARM outperforms the MSN and ShuffleNet in many aspects and suggest some plausible applications of the D-ARM networks, e.g., broadband switching architecture, multiprocessor connection, high-speed MAN, WDM optical networks and photonic networks.